BIODIVERSITY OF ZOOPLANKTON COMMUNITY IN COASTAL AREA OF SON TRA PENINSULA, DA NANG - Truong, Trinh Si-Hai; Nguyen, Vinh Tam (Vietnam Journal of Marine Science and Technology, 2019)
Zooplankton samples were collected at 16 stations in the coastal waters of Son Tra peninsula, Da Nang city in dry season (7/2016). At each station, zooplankton samples were collected by using Juday net (mouth diameter: 37 cm, mesh-zise: 200 µm) from 1 m above bottom to surface. 112 species belonging to 11 zooplankton groups were identified. Copepod was a dominant group with 67 species, followed by Tunicate (13) and Gastropod (7). The Northeast and Northwest areas of Son Tra peninsula have a higher biodiversity than the South and Southeast based on number of species, species richness value. An average density of zooplankton was 7.768 ins.m-3 and was decided by copepod density (3.759 inds.m-3 on average). Station 4 had the highest number of individual and station 18 had the lowest zooplankton density. Oikopleura fusiformis was dominant in most of stations in the north area (22.16%) and in the northwest (15.97%), while copepod species Paracalanus crassirostris was dominant in the northwest (16.51%) and in the south (24.57%) of Son Tra based on SIMPER analysis (90%).